2010
DOI: 10.1149/1.3484816
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Selenium from the 1-Ethyl-3-Methylimidazolium Chloride-Tetrafluoroborate Room-Temperature Ionic Liquid

Abstract: Electrodeposition of the selenium film in 1-ethyl-3-methylimidazolium chloride-tetrafluoroborate ionic liquid containing excess chloride ions on indium tin oxide (ITO) coated glass electrodes was studied at 30 o C. Cyclic voltammogrammetric results indicate that the reduction reaction of Se(IV) to Se (0) is not a simple four-electron reduction. Scanning electron microscopy reveals that the morphology of the selenium deposits is affected by the applied deposition potential and X-ray powder diffraction data indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Feng et al [71] proposed a template-free one-step electrochemical synthesis method of CdSe nanowires with hexagonal structure in dimethylformamide (DMF) containing CdCl 2 and elemental Se. Chou et al [72] discovered that a dense t-Se layer could be deposited on the ITO electrode in [C 2 mim][BF 4 ]/[C 2 mim]Cl. It is worth noting that since Se is a semiconductor, Se deposited at lower temperatures can lead to decreasing rate in the subsequent electrodeposition.…”
Section: Se Electrodeposition In An Ionic Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al [71] proposed a template-free one-step electrochemical synthesis method of CdSe nanowires with hexagonal structure in dimethylformamide (DMF) containing CdCl 2 and elemental Se. Chou et al [72] discovered that a dense t-Se layer could be deposited on the ITO electrode in [C 2 mim][BF 4 ]/[C 2 mim]Cl. It is worth noting that since Se is a semiconductor, Se deposited at lower temperatures can lead to decreasing rate in the subsequent electrodeposition.…”
Section: Se Electrodeposition In An Ionic Liquidmentioning
confidence: 99%
“…Increasing the potential and the temperature can effectively improve the crystallinity and density of the deposited Se film. Chou et al [72] investigated the electrodeposition of Se film on ITO coated glass electrode in an ionic liquid containing excess chloride ions. It was found that the deposition of crystalline Se required a more negative deposition potential.…”
Section: Se Electrodeposition In An Ionic Liquidmentioning
confidence: 99%
“…In the past decade ionic liquids have gained attention as an alternative electrolyte media for the electrodeposition of various semiconductors and reactive metals, such as Ge, Si, Ta, and Al, due to their large electrochemical windows and low volatility . Several groups have developed methods to deposit both amorphous and metallic selenium using several ionic liquids and Se precursors. In 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide at temperatures >100 °C a trigonal Se (t-Se) deposit was obtained from SeCl 4 . Deposition using SeCl 4 or SeO 2 in 1-ethyl-3-methylimdazolium tetrafluoroborate/chloride at temperatures >100 °C produced single crystal nanowires of t-Se from SeO 2 and an amorphous selenium (a-Se) deposit from SeCl 4 .…”
Section: Introductionmentioning
confidence: 99%
“…But the resulting wastewater containing several intermediate products (Na 2 SeO 3 or H 2 SeO 3 ) causes a great loss of Se resources. As a low-cost and environmentally friendly method for preparing Se, electrochemical methods under different systems [10][11][12][13][14] have attracted attention from researchers.…”
mentioning
confidence: 99%